Studi Kasus tentang Peran Guru Bimbingan Konseling dalam Menangani Masalah Disiplin Siswa di MTsS Al-Washliyah Tembung - Muhammad Arby Fahrezi; Rizka Amanda Putri; Saila Rahma Annisa Nasution; Abdul Fattah Nasution (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to describe the role of Guidance and Counseling (BK) teachers in addressing student discipline issues at MTsS Al-Washliyah Tembung. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation. The findings reveal that BK teachers serve not only as enforcers of school rules but also as character educators through both individual and group counseling strategies. These strategies include open dialogue, parental involvement, and the application of educational rather than punitive sanctions. Challenges faced include limited parental engagement, time constraints in providing counseling services, and students’ uncooperative behavior. The study highlights that effective discipline development is influenced by active involvement of BK teachers, inter-party collaboration, and humanistic approaches. The findings provide insights for improving character-building programs in educational institutions.